Effect of saline organic acid solutions applied during soft wheat tempering on microbial load and flour functionality. Issue 6 (4th October 2019) - Sabillón, Luis; Stratton, Jayne; Rose, Devin; Bianchini, Andréia
Abstract: Background and objectives: In recent years, special concern has been raised about the safety of wheat‐based products. In light of several incidents of foodborne illness associated with flour, the objectives of this study were designed to (a) evaluate the efficacy of saline organic acids solutions to reduce the natural microbiota of soft wheat grain and flour, and (b) to assess the impact of these tempering solutions on the functional properties of soft wheat flour. Findings: The microbial load of the tempered wheat was significantly reduced by all saline organic acid treatments. The combination of 5.0% lactic acid–NaCl was the most effective against aerobic mesophilic bacteria and Enterobacteriaceae, with average reductions of 3.1 ± 0.1 and 4.5 ± 0.0 log CFU/g, respectively. In addition, this tempering solution yielded flour with a significantly lower microbial load compared with the control. Tempering with saline organic acid solutions did result in minor, but significant, variations in the solvent retention capacity profile of some flours. However, the treatments did not cause significant changes in the pasting profile of flours or in the physical characteristics and texture profile of baked cookies. Conclusions: The addition of organic acids and NaCl to the tempering water improved the microbiological quality of the wheat grain and the resulting flour without compromising its functionality. Significance and novelty: This study evaluates the inclusion of antimicrobial agents in the water used to temper wheat grain prior to milling as a practical method to reduce the number of microbial contaminants in flour and flour‐based foods that are at risk for consumption without cooking or any killing step.